APPLICATION OF CLASH DETECTION ANALYSIS IN APARTMENT BUILDING - Rakha Radhitya Putra Yudiyanto; Lila Ayu Ratna Winanda; Hadi Surya Wibawanto Sunarwadi; Deviany Kartika (Jurusan Pendidikan Teknologi Dan Kejuruan, 2025)
The advancement of technology in Indonesia can be felt by many business people, one of which is from the construction sector. which used to use conventional methods including in the modeling process, as well as the error analysis process during the construction project planning process. error analysis process during the construction project planning process, because conventional methods tend to take a long time and have a low level of accuracy. low level of accuracy. Therefore, this research was carried out using the integration of between Building Information Modeling (BIM) using Clash Detection analysis to show the clash of Detection analysis to show the clash that occurs between the structure and the architecture of the building to be planned to avoid errors. architecture of the building to be planned in order to avoid errors based on integration between Autodesk Revit and Autodesk Naviswork. By Clash Detection analysis obtained the results, the clash that clashes that occurred as many as 298 clashes, which means that clashes have been found between components that can reduce the efficiency of components that can reduce development efficiency in construction projects